Haemophilia B: impact on patients and economic burden of disease - Gater, Adam; Thomson, Thomas A.; Strandberg-Larsen, Martin (Thrombosis and Haemostasis, 2011)
Worldwide, haemophilia is the most common hereditary bleeding disorder. The incidence of haemophilia B, however, is considerably less than haemophilia A and consequently appears to have received less attention in the research literature. This article aims to summarise the available evidence documenting the patient and economic burden associated with haemophilia B and current methods of disease management. Both the immediate and long-term clinical consequences of haemophilia B can have significant implications for patients in terms of functional limitations and diminished health-related quality of life (HRQOL). Evidence demonstrates that primary prophylaxis is the optimal strategy for replacing missing clotting factor IX (FIX) and managing haemophilia B. Use of recombinant FIX (rFIX) over plasma-derived FIX (pd-FIX) is also generally preferred for safety reasons. Prophylaxis using currently available rFIX products, however, requires a demanding regimen of intravenous infusions 2–3 times a week which may have significant implications for adherence and ultimately the long-term efficacy of such regimens. Only limited assessments of the cost-effectiveness of prophylactic versus on-demand FIX treatment regimens have been conducted to date. Prophylaxis, however, is generally more costly as greater quantities of FIX are consumed. Any reduction in FIX replacement dosing frequency is expected to improve patient adherence and contribute to improved clinical outcomes, further supporting the costeffectiveness of such interventions. Although a rare disease, as economic constraints for healthcare increase, generating further information regarding the key clinical, patient and economic outcomes associated with haemophilia B will be essential for supporting improvements in care for people with haemophilia B.
Keywords: Burden; cost-effectiveness; factor IX; haemophilia B; health-related quality of life